The Effect of Chart Type on Pilots' Response Time. (September 2017) - Milner, Mattie N.; Bush, Dylan; Marte, Daniel; Rice, Stephen; Winter, Scott; Adkins, Evan; Roccasecca, Angela; Tamilselvan, Gajapriya
Electronic flight bags have become common place in commercial and general aviation flight decks. These tools provide for a compact and concise methods of carrying charts, procedure manuals, policies, and flight-related communications. On devices with connectivity, these tools can even be used to download real-time weather and file flight plans or even serve as a moving map by connecting a portable GPS receiver. However, with the proliferation of these devices, few studies have searched for any performance differences in pilots between these electronic charts and traditional paper charts. The purpose of this study was to compare pilots response time when answering a series of 30 questions related to instrument approach procedures using an electronic chart display, followed by paper charts. Twenty-seven instrument flight rated participants completed the repeated measures design using a desktop computer. The study simulated an event where the pilot's electronic flight bag failed, and they had to use paper charts as a backup. The results of the study suggest a significant increase in participant response time when using paper charts compared to electronic ones. Participants response time using paper chart also did not significantly increase from their first trial using paper to their last trial using paper. Additional research should be completed to explore this relationship further and determine if the use of electronic charts are resulting in an unintended degradation of other pilot skills.